MANAJEMEN KELEMBAGAAN MASYARAKAT DESA DALAM MENYEBARKAN INFORMASI MEDIA MASSA (Studi Kasus di Kota Batu) - Mondry, Mondry (Jurnal Interaktif, 2010)
This research aims to acknowledge the usage of information served by the media in rural institution society. In this proposal, usage means steps that have been conducted by rural institutions on managing and disbursing the information to entire society. The advancment of media and technology in particular local media leads to the contribution of the wide-range information that may useful to the intended society. This research appllies qualitative method focusing on rural society institution management in terms of disbursing information. Respondent will be firmed purposively. It means the head of household to achieve intended information by using mass media. Related elements that have been researched are neighbouring contacts, form the RW, RW and local head village and ulama. The result, institutional society in rural have not yet contribute to manage information by the media. The information by the media is still considered as personal business. Â Key words:Â  mass media, rural institution society